Predicting positive food challenges in children sensitised to peanuts/tree nuts. Issue 3 (3rd April 2013) - Ludman, Sian; Ballabeni, Pierluigi; Eigennman, Philippe A.; Wassenberg, Jacqueline
Abstract Background Children with atopic diseases in early life are frequently found with positive IgE tests to peanuts/tree nuts without a history of previous ingestion. We aimed to identify risk factors for reactions to nuts at first introduction. Methods A retrospective case‐note and database analysis was performed. Recruitment criteria were: patients aged 3–16 yr who had a standardized food challenge to peanut and/or tree nuts due to sensitisation to the peanut/tree nut (positive spIgE or SPT) without previous consumption. A detailed assessment was performed of factors relating to food challenge outcome with univariate and multivariate logistic regression analysis. Results There were 98 food challenges (47 peanut, 51 tree nut) with 29 positive, 67 negative and 2 inconclusive outcomes. A positive maternal history of allergy and a specific IgE >5 kU/l were strongly associated with a significantly increased risk of a positive food challenge (OR 3.73; 95% CI 1.31–10.59; p = 0.013 and OR 3.35; 95% CI 1.23–9.11; p = 0.007, respectively). Adjusting for age, a three year‐old with these criteria has a 67% probability of a positive challenge. There was no significant association between types of peanut/tree nut, other food allergies, atopic conditions or severity of previous food reactions and positive challenges. Conclusions We have demonstrated an association between the presence of maternal atopic history and a specific IgE >5 kU/l, with a significant increase in the likelihood of a positive food challenge. Although requiring further prospective validation these easily identifiable components should be considered when deciding the need for a challenge.